Transformasi Pembelajaran PAI untuk Anak Usia Dini melalui Project Based Learning Berbasis Teknologi - Titien Koesoemawati; Defi Lia Amanda; Dina Mardiana (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to describe how technology-enhanced Project Based Learning (PjBL) can transform Islamic Religious Education (PAI) for early childhood learners. Using a qualitative approach involving participatory observations, in-depth interviews, and documentation, this research analyzes the implementation of PjBL at TK ABA 2 Cepu through the Technological Pedagogical Content Knowledge (TPACK) framework and examines its contribution to strengthening Islamic values and early childhood spirituality. The findings show that the integration of simple technologies—such as educational videos, digital drawing tablets, and interactive quizzes—effectively concretizes abstract religious concepts, enhances children’s participation, and reinforces character development and Islamic digital literacy. PjBL creates learning experiences that are more active, collaborative, and meaningful, enabling Islamic values to be internalized through contextual projects aligned with children’s developmental stages. These results affirm that purposeful technological integration can serve as an effective spiritual and pedagogical medium in PAI instruction and offer both practical and theoretical implications for developing PAI learning models in early childhood education.